PENGARUH WAKTU DAN SUHU GLISEROLISIS TERHADAP SIFAT KIMIA MONO-DIASILGLISEROL PADA SKALA PILOT PLANT - Arief R. Affandi; Nuri Andarwulan; Purwiyatno Hariyadi (Jurnal Teknologi dan Industri Pangan, 2017)
Mono and Diacylglycerol (MDAG) is one of the food additives that can be used for stabilizing food emulsion system. MDAG is commercially manufactured through glycerolysis reaction at high temperatures and catalyzed by inorganic alkaline such as NaOH. This process results in an equilibrium mixture containing partial glycerol esters and excess of glycerol. The present study describes the effect of reaction temperature and time in a 50 kg-pilot plant production on the chemical properties of the resulting MDAG emulsifier. Fully hydrogenated palm stearin (FHPS) and NaOH were used as the substrate and catalyst, respectively. The production was conducted following a factorial experiment in a completely randomized design with two variable combinations, i.e. temperatures at 170, 180, and 185°C; and times of 120 and 180 min. Each experiment combination was conducted in two replications. The glycerolysis reaction at 180°C for 180 min produced the highest yield of MDAG, i.e. 87.2±1.41%, which comprised of 48.78±2.28% monoacylglycerol (MAG), 30.92±1.23% diacylglycerol (DAG), 4.79±0.61% triacylglycerol (TAG), 1.97±0.04% free fatty acid (FFA), and 2.35±0.05% free glycerol.